Alternative agents to prophylactic platelet transfusion for preventing bleeding in people with thrombocytopenia due to chronic bone marrow failure: a meta-analysis and systematic review - Desborough, Michael; Hadjinicolaou, Andreas V; Chaimani, Anna; Trivella, Marialena; Vyas, Paresh; Doree, Carolyn; Hopewell, Sally; Stanworth, Simon J; Estcourt, Lise J (Cochrane database of systematic reviews, 2016)
People with thrombocytopenia due to bone marrow failure are vulnerable to bleeding. Platelet transfusions have limited efficacy in this setting and alternative agents that could replace, or reduce platelet transfusion, and are effective at reducing bleeding are needed. To compare the relative efficacy of different interventions for patients with thrombocytopenia due to chronic bone marrow failure and to derive a hierarchy of potential alternative treatments to platelet transfusions. We searched for randomised controlled trials (RCTs) in the Cochrane Central Register of Controlled Trials (the Cochrane Library 2016, Issue 3), MEDLINE (from 1946), Embase (from 1974), CINAHL (from 1937), the Transfusion Evidence Library (from 1980) and ongoing trial databases to 27 April 2016. We included randomised controlled trials in people with thrombocytopenia due to chronic bone marrow failure who were allocated to either an alternative to platelet transfusion (artificial platelet substitutes, platelet-poor plasma, fibrinogen concentrate, recombinant activated factor VII (rFVIIa), desmopressin (DDAVP), recombinant factor XIII (rFXIII), recombinant interleukin (rIL)6 or rIL11, or thrombopoietin (TPO) mimetics) or a comparator (placebo, standard of care or platelet transfusion). We excluded people undergoing intensive chemotherapy or stem cell transfusion. Two review authors independently screened search results, extracted data and assessed trial quality. We estimated summary risk ratios (RR) for dichotomous outcomes. We planned to use summary mean differences (MD) for continuous outcomes. All summary measures are presented with 95% confidence intervals (CI).We could not perform a network meta-analysis because the included studies had important differences in the baseline severity of disease for the participants and in the number of participants undergoing chemotherapy. This raised important concerns about the plausibility of the transitivity assumption in the final dataset and we could not evaluate transitivity statistically because of the small number of trials per comparison. Therefore, we could only perform direct pairwise meta-analyses of included interventions.We employed a random-effects model for all analyses. We assessed statistical heterogeneity using the I statistic and its 95% CI. The risk of bias of each study included was assessed using the Cochrane 'Risk of bias' tool. The quality of the evidence was assessed using GRADE methods. We identified seven completed trials (472 participants), and four ongoing trials (recruiting 837 participants) which are due to be completed by December 2020. Of the seven completed trials, five trials (456 participants) compared a TPO mimetic versus placebo (four romiplostim trials, and one eltrombopag trial), one trial (eight participants) compared DDAVP with placebo and one trial (eight participants) compared tranexamic acid with placebo. In the DDAVP trial, the only outcome reported was the bleeding time. In the tranexamic acid trial there were methodological flaws and bleeding definitions were subject to significant bias. Consequently, these trials could not be incorporated into the quantitative synthesis. No randomised trial of artificial platelet substitutes, platelet-poor plasma, fibrinogen concentrate, rFVIIa, rFXIII, rIL6 or rIL11 was identified.We assessed all five trials of TPO mimetics included in this review to be at high risk of bias because the trials were funded by the manufacturers of the TPO mimetics and the authors had financial stakes in the sponsoring companies.The GRADE quality of the evidence was very low to moderate across the different outcomes.There was insufficient evidence to detect a difference in the number of participants with at least one bleeding episode between TPO mimetics and placebo (RR 0.86, 95% CI 0.56 to 1.31, four trials, 206 participants, low-quality evidence).There was insufficient evidence to detect a difference in the risk of a life-threatening bleed between those treated with a TPO mimetic and placebo (RR 0.31, 95% CI 0.04 to 2.26, one trial, 39 participants, low-quality evidence).There was insufficient evidence to detect a difference in the risk of all-cause mortality between those treated with a TPO mimetic and placebo (RR 0.74, 95%CI 0.52 to 1.05, five trials, 456 participants, very low-quality evidence).There was a significant reduction in the number of participants receiving any platelet transfusion between those treated with TPO mimetics and placebo (RR 0.76, 95% CI 0.61 to 0.95, four trials, 206 participants, moderate-quality evidence).There was no evidence for a difference in the incidence of transfusion reactions between those treated with TPO mimetics and placebo (pOR 0.06, 95% CI 0.00 to 3.44, one trial, 98 participants, very low-quality evidence).There was no evidence for a difference in thromboembolic events between TPO mimetics and placebo (RR 1.41, 95%CI 0.39 to 5.01, five trials, 456 participants, very-low quality evidence).There was no evidence for a difference in drug reactions between TPO mimetics and placebo (RR 1.12, 95% CI 0.83 to 1.51, five trials, 455 participants, low-quality evidence).No trial reported the number of days of bleeding per participant, platelet transfusion episodes, mean red cell transfusions per participant, red cell transfusion episodes, transfusion-transmitted infections, formation of antiplatelet antibodies or platelet refractoriness.In order to demonstrate a reduction in bleeding events from 26 in 100 to 16 in 100 participants, a study would need to recruit 514 participants (80% power, 5% significance). There is insufficient evidence at present for thrombopoietin (TPO) mimetics for the prevention of bleeding for people with thrombocytopenia due to chronic bone marrow failure. There is no randomised controlled trial evidence for artificial platelet substitutes, platelet-poor plasma, fibrinogen concentrate, rFVIIa, rFXIII or rIL6 or rIL11, antifibrinolytics or DDAVP in this setting.